2003
DOI: 10.1016/s0016-6480(03)00191-6
|View full text |Cite
|
Sign up to set email alerts
|

Divergence of endocrine and metabolic responses to stress in two rainbow trout lines selected for differing cortisol responsiveness to stress

Abstract: Abstract. Rainbow trout (Oncorhynchus mykiss) of two lines selected for low (LR) and high (HR) cortisol stress-responsiveness were subjected to confinement for a period of 336 hours.Endocrine (plasma cortisol, hepatic cortisol binding) and metabolic (plasma glucose, lactate, amino acids; hepatic glycogen and alanine aminotransferase levels) indices of stress were measured at intervals in confined and unconfined fish of both lines. During confinement plasma cortisol concentration reached maximum values earlier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(49 citation statements)
references
References 55 publications
5
44
0
Order By: Relevance
“…In the present study, when subjected to a 1 hour confinement stressor, fish from the two lines exhibited a markedly divergent plasma cortisol response. This finding was consistent with previous studies on the F2 generation (Pottinger and Carrick, 2001;Trenzado, et al, 2003) and indicated that the behavioural comparisons carried out during the present study had indeed contrasted two groups of fish with a pronounced difference in HPI-axis reactivity.…”
Section: Stress Responsivenesssupporting
confidence: 94%
“…In the present study, when subjected to a 1 hour confinement stressor, fish from the two lines exhibited a markedly divergent plasma cortisol response. This finding was consistent with previous studies on the F2 generation (Pottinger and Carrick, 2001;Trenzado, et al, 2003) and indicated that the behavioural comparisons carried out during the present study had indeed contrasted two groups of fish with a pronounced difference in HPI-axis reactivity.…”
Section: Stress Responsivenesssupporting
confidence: 94%
“…However, electroshock-exposed fish increased glucose without a correlated cortisol increase, thus suggesting that other factors are involved. This suggestion should be clarified in future investigations, also because controversial results have been reported regarding cortisol-regulated glucose levels: cortisol was reported to decrease (38) or not to affect (39) glucose levels, and Trenzado et al (40) reported that low-cortisol responding rainbow trout had higher glucose increase than high-cortisol responding fish.…”
Section: Discussionmentioning
confidence: 98%
“…From earlier research, we know that LR fish are capable of mounting a cortisol response to stress [e.g., confinement stress, ϳ40 -100 ng/ml (40,50,52)], but they did not do so during acute heat shock. It has been suggested that HR and LR fish may not differ in the scope of cortisol induction during stress, but rather in the dynamic of the cortisol response (50,52). While this may be the case for confinement stress, it does not appear to be so for heat shock where LR fish failed to exhibit appreciable increases in plasma cortisol levels over the course of our experiment.…”
Section: Discussionmentioning
confidence: 99%